Novel approaches to improve estimates of short-lived halocarbon emissions during summer from the Southern Ocean using airborne observations - Asher, Elizabeth; Hornbrook, Rebecca S.; Stephens, Britton B.; Kinnison, Doug; Morgan, Eric J.; Keeling, Ralph F.; Atlas, Elliot L.; Schauffler, Sue M.; Tilmes, Simone; Kort, Eric A.; Hoecker-Martínez, Martin S.; Long, Matt C.; et al. (Atmospheric Chemistry and Physics, 2019)
Fluxes of halogenated volatile organic compounds (VOCs) over the Southern Ocean remain poorly understood, and few atmospheric measurements exist to constrain modeled emissions of these compounds. We present observations of CHBr3, CH2Br2, CH3I, CHClBr2, CHBrCl2, and CH3Br during the O2∕N2 Ratio and CO2 Airborne Southern Ocean (ORCAS) study and the second Atmospheric Tomography mission (ATom-2) in January and February of 2016 and 2017. Good model–measurement correlations were obtained between these observations and simulations from the Community Earth System Model (CESM) atmospheric component with chemistry (CAM-Chem) for CHBr3, CH2Br2, CH3I, and CHClBr2 but all showed significant differences in model : measurement ratios. The model : measurement comparison for CH3Br was satisfactory and for CHBrCl2 the low levels present precluded us from making a complete assessment. Thereafter, we demonstrate two novel approaches to estimate halogenated VOC fluxes; the first approach takes advantage of the robust relationships that were found between airborne observations of O2 and CHBr3, CH2Br2, and CHClBr2. We use these linear regressions with O2 and modeled O2 distributions to infer a biological flux of halogenated VOCs. The second approach uses the Stochastic Time-Inverted Lagrangian Transport (STILT) particle dispersion model to explore the relationships between observed mixing ratios and the product of the upstream surface influence of sea ice, chl a, absorption due to detritus, and downward shortwave radiation at the surface, which in turn relate to various regional hypothesized sources of halogenated VOCs such as marine phytoplankton, phytoplankton in sea-ice brines, and decomposing organic matter in surface seawater. These relationships can help evaluate the likelihood of particular halogenated VOC sources and in the case of statistically significant correlations, such as was found for CH3I, may be used to derive an estimated flux field. Our results are consistent with a biogenic regional source of CHBr3 and both nonbiological and biological sources of CH3I over these regions.